Business Economic Feasibility and Fishermen Bagan Perahu (Lift Net) in Pelita Jaya Bay of Maluku Province - Nurlette, Hartono (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
Bagan Perahu (Lift Net) is a fishing business that requires a large investment value. The income of this business is uncertain because it relies heavily on catches and the fish season. The risk of uncertainty will affect business income and fishermen's income. This study aims to analyze the economic feasibility of fisheries and fishermen's businesses in Pelita Jaya Bay West Seram Regency, Maluku. The method used in this study is a survey. The results showed that the business carried out is still very profitable, seen from the business income earned by the owner, which is Rp68,548,000/year. Financial analysis shows the value of NPV over the next ten years amounting to Rp241,568,753; the value of IRR is still above the current bank interest rate of 42.98% and the net value of B/C>1, which is 2.58. The average monthly fishermen's income amounted to Rp1,288,311, and the existing income is still far below the UMR of Maluku Province. This is certainly not economically viable.